(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Ni(II) chloride reacts with tetrathiazyldihydrofluoride in an organic medium to give sold composition of the complex (S4N4H2F2)2 NiCl2.The complex has been shown by physicohemical methods to be bidentated N-coordinated complex having distorted Oh geometry and paramagnetic character. Key Words: Tetra sulphur tetranitride; Tetrathiazyl dihydrofluoride; N-coordinated complex DOI: 10.3329/bjsir.v44i4.4603 Bangladesh J. Sci. Ind. Res. 44(4), 485-487, 2009